Apropriação das tecnologias de informação e comunicação em bibliotecas escolares em busca de um espaço dinâmico - Lanzi, Lucirene Andréa Catini [UNESP] (2012)
The school library should be inserted in the educational context. But this is not the reality that is observed in practice. Throughout its history the school library has always been regarded by students as a boring place, stagnant and things related to outdated, since teachers and education professionals often consider it a dull and outdated space. The ideal is to make the library part of the educational context, share responsibility for the teaching-learning process and training of students‟ information literacy. One way of achieving this is to insert digital collaborative environments in the school library and encourage learners to share this transformation through knowledge encouragement and motivation. Assuming that the school librarian besides being a mediator of information, is also an employee/educator and as such need to use educational resources to better cognitive assimilation by the students/learners, this study has as main objective to present the current Information and Communication Technologies in the routine of a school library in the educational space and provide references and experiences that demonstrate Information and Communication Technologies (ICT) can be combined with the acquisition of academic knowledge and culture for students, improving their information literacy and why not, also digital. This study also aimed to specific present and structure information environments appropriate to promote the revitalization of the library space, seeking to make it a participatory and referential environment for study, search and update students, enhance information literacy/digital and the collaborative construction along with students of digital environments. Therefore it was used as theoretical basis, Piaget's theory which explains how the steps of knowledge assimilation and accommodation... (Complete abstract click electronic access below)